Added value of electromyography in the diagnosis of myopathy: A consensus exercise. Issue 5 (May 2017) - Pugdahl, K.; Johnsen, B.; Tankisi, H.; Camdessanché, J.P.; de Carvalho, M.; Fawcett, P.R.W.; Labarre-Vila, A.; Liguori, R.; Nix, W.; Schofield, I.; Fuglsang-Frederiksen, A.
Highlights: In a European multicentre study, electrodiagnostic medicine (EDX) results increased the consensus probability of myopathy. Adding EDX results increased the diagnostic certainty of myopathy in one third of 195 patients. The highest diagnostic impact of EDX was seen in myopathies of unknown aetiology. Abstract: Objective: Currently, neurologists may primarily rely on blood biomarkers, muscle biopsy, MRI, and genetics in the diagnostic work-up of suspected myopathy. Using expert consensus as diagnostic reference standard, this study addressed the added value of electrodiagnostic medicine (EDX) in diagnosis of myopathies. Methods: One hundred ninety-four EDX evaluations of patients with a peer-review consensus diagnosis of myopathy were collected by seven European centres. Each patient was given three different consensus diagnoses: (1) the EDX diagnosis solely based on EDX results, (2) the pure clinical diagnosis based on all available information except EDX results, and (3) the final diagnosis including EDX and all additional information. The myopathies were grouped as muscular dystrophy (45), inflammatory myopathy (46), other aetiology (36) or unknown aetiology (67). Results: Higher diagnostic probabilities for myopathy were seen in the final diagnosis compared to the pure clinical diagnosis ( p < 0.001). Adding EDX information increased the diagnostic probability of myopathy in 67 patients (34.4%). The greatest increase was seen for myopathies of unknown aetiology. Conclusions: EDX has a major impact in the diagnosis of myopathies of unknown aetiology. In genetically or biopsy proven myopathies, EDX generally supports the diagnosis. Significance: EDX is still a useful tool in the diagnostic work-up of most patients with suspected myopathy.